ANALISIS KESULITAN GURU MATEMATIKA DALAM PEMBELAJARAN DI SEKOLAH BERBASIS PESANTREN PADA MASA PANDEMI COVID-19 - Mariyati Wulan Dari; Lisma Dian Kartika Sari; ahmad hafas rasydi (PENDIDIKAN SAINS DAN TEKNOLOGI, 2022)
Coronavirus Diseases 2019 (COVID-19) is a worldwide epidemic. The Covid-19 outbreak has an impact on the world of education, one of which is at MA Sarji Ar-Rasyid which is a boarding school-based school. In this case, it is necessary to conduct research to find out the difficulties experienced or faced by the MA mathematics teacher Sarji Ar-Rasyid in learning challenges during the Covid-19 pandemic. This type of research is a qualitative with a qualitative descriptive approach. Data sources include primary data sources, namely interviews and secondary data sources, supporting research data. The selected data source is Mathematics Teacher. Data was collected by means of observation, interviews and documentation. The data analysis techniques used were data reduction, data display, and conclusion drawing and verification. The results of the study are that the school remains active as usual, but students do not wear uniforms but use ordinary Muslim clothes. Learning is done offline / face to face. Difficulties or obstacles for mathematics teachers in learning during the Covid-19 pandemic, namely the decrease in student enthusiasm for learning, the decrease in the level of teacher attendance.